A case study of incarcerated males participating in a canine training program - Currie, Nikki S. (Kansas State University, 2008)
The number of animal training programs in correctional facilities has increased in the past 25 years. Anecdotal accounts have informally assessed the efficacy of prison training programs; however, only limited systemic studies have been conducted (Britton & Button, 2005; Furst, 2006). Preliminary information from anecdotal accounts and narratives indicates the potential these programs have to impact inmate behavior, self- esteem, staff and inmate morale, and community perceptions of offenders (Cushing & Williams, 1995; Harkrader, Burke, & Owen, 2004). There is also an indication inmate trainers learn responsibility, patience, coping skills, and vocational skills (Britton & Button, 2005; Merriam-Arduini, 2000; Turner, 2007). This qualitative study presents preliminary findings from the following five participant perspectives on the perceived outcomes of a canine training program in a correctional facility where inmates train assistance, therapy, rescue, and medical alert canines: (a) inmate trainers, (b) former inmate trainers, (c) non-trainer inmates who are not involved in the training program, (d) staff, and (e) the researcher. Once trained, the canines are adopted as assistance dogs for individuals in need. Data collected from in- depth interviews with current inmate trainers, former inmate trainers, non-trainer inmates, and staff, and audio and video recordings, researcher observations, and a researcher developed scale indicated the following themes which emerged from the study: there are positive emotional outcomes and positive practical outcomes for inmate trainers who work with dogs in the training program. Positive emotional outcomes for inmate trainers include the following: (a) providing social support, (b) gaining a sense of pride, (c) serving as a feeling of giving back to society, (d) increasing personal patience, (e) humanizing the inmate trainers, and (f) improving self-esteem. Positive practical outcomes for inmate trainers emerged in the following areas: (a) improving responsibility, (b) having a positive impact on the prison environment, (c) providing opportunities to help others, (d) using goal setting, (e) gaining employability skills, and (e) having a positive effect on behavior. Results from this study will add to existing literature and research in the field of animal-assisted interventions and rehabilitation programs with human beings, specifically those in correctional facilities. In addition, results from this study will assist correctional administration in the design, implementation, and evaluation of dog training programs in prisons.
Keywords: Prison animal programs; Human-animal bond; Pet-facilitated therapy; Correctional facilities; Pet therapy; Prison programs; Education, Guidance and Counseling (0519); Sociology, Criminology and Penology (0627)